2008
DOI: 10.1002/rcm.3705
|View full text |Cite
|
Sign up to set email alerts
|

Rapid‐resolution liquid chromatography/mass spectrometry for determination and quantitation of polyphenols in grape berries

Abstract: A rapid-resolution liquid chromatography/mass spectrometric (RRLC/MS) method for detection and quantitation of polyphenols in grape berry skins and seeds has been developed. Pulp-free berry skins were treated with liquid nitrogen and ground; seeds were also ground. Then, 3 g of samples were extracted with 30 mL of a mixture of methanol/water/formic acid 70:30:1 (v/v/v) under sonication and 1 microL of the final extract was injected into two 100 x 2.1 mm i.d., 1.8 microm Zorbax Eclipse plus C18 columns connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 60 publications
5
63
0
Order By: Relevance
“…We investigated the impact of the matrix effect on our analysis as described by Cavaliere et al (2008) and found that most of the curves (representing 80% of the identified metabolites) reached a plateau at higher dilutions, allowing us to calculate a correction factor. It was not possible to obtain a reliable correction factor for the other compounds, but most of this group comprised low-abundance metabolites.…”
Section: Annotation Of Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated the impact of the matrix effect on our analysis as described by Cavaliere et al (2008) and found that most of the curves (representing 80% of the identified metabolites) reached a plateau at higher dilutions, allowing us to calculate a correction factor. It was not possible to obtain a reliable correction factor for the other compounds, but most of this group comprised low-abundance metabolites.…”
Section: Annotation Of Metabolitesmentioning
confidence: 99%
“…The matrix effect for all putatively identified compounds was evaluated as described by Cavaliere et al (2008). Sample extracts were diluted with the extraction solvent (undiluted, 1:2, 1:5, 1:10, 1:25 and 1:50) and 10 ll of each dilution were analyzed in duplicate by HPLC-MS.…”
Section: Evaluation Of Matrix Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were directly identified in the flavonoid fraction by HPLC co-injection with standards and through the negative ions observed in the direct infusion ESI-MS of the flavonoid fraction. Quasimolecular ions at m/z 289 (compounds 1 and 2) and m/z 477 (compound 6; MS/MS 477, 301) were observed in the negative ESI mass spectra of the flavonoid fraction (Charrouf et al, 2007;Cavaliere et al, 2008). (Foo et al, 2000;Zhang et al, 2003;He et al, 2007, Li & Deinzer, 2007.…”
Section: Flavonoid Fractionmentioning
confidence: 99%
“…Their concentration and composition in grapes depends on the cultivar and so it is influenced by viticultural and environmental factors, such as climate conditions, maturity stage, and production area [3][4][5][6]. Polyphenols exhibit beneficial effects on human health thanks to the strong free radical scavenging and antioxidant activity, as well as cardioprotective, vasodilatatory, anticarcinogenic, anti-inflammatory, antiallergic, antibacterial, immune-stimulating, antiviral, and 2 ISRN Analytical Chemistry estrogenic properties [7][8][9].…”
Section: Introductionmentioning
confidence: 99%